Export policies and performance in Israel - Richard Pomfret (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1975)
The aims of this paper are firstly to present a unified description of the Israeli government's export policies and of the growth and composition of Israel's exports and secondly to provide macroeconomic analysis of her export performance. The first section outlines the major policies which the government has adopted to promote exports. In sections 2 and 3 the trends in the volume and composition of exports are described and comparisons made with other countries. The constant market shares model is then used in section 4 to identify the .sources of Israel's export growth in the 1960s. In the final two sections exports are divided into two groups, non-manufactured goods (plus diamonds) and manufactured goods. Greater attention is paid to the latter category, since this is the area in which Israel's prospects for future export expansion are brightest and since it is also the more fruitful category for finding lessons for LDCs seeking to expand exports. Analysis of the factors behind the expansion of Israel's manufactured exports is carried out by means of constant market share analysis and econometric estimation of the aggregate supply function of manufactured exports.
Keywords: 330